PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL BERDASARKAN UU NOMOR 2 TAHUN 2004 - Dahlia & Agatha Jumiati (Wacana Hukum, 2011)
AbstractIndustrial dispute solving that managed in UU No. 2 Tahun 2004 can be solved by bipartite negotiation, conciliation, arbitartion, mediation, and industrial dispute court. Principe of this mattter is to prior bipartite negotiation as the first step before go to other way. As it managed in UU No. 2 Tahun 2004 it suppose to be everyone that related can solve fast, fair, and cheaply. Key words: industrial relation, industrial dispute, and industrial dispute solving.